Characteristic Features of the Evolution of a Meiyu Frontal Rainstorm with Doppler Radar Data Assimilation. (23rd October 2018) - Li, Hongli; Hu, Yang; Zhou, Zhimin; Peng, Juxiang; Xu, Xiangde
Abstract : During the Meiyu period, floods are prone to occur in the middle and lower reaches of the Yangtze River because of the highly concentrated and heavy rainfall, which caused huge life and economic losses. Based on numerical simulation by assimilating Doppler radar, radiosonde, and surface meteorological observations, the evolution mechanism for the initiation, development, and decaying of a Meiyu frontal rainstorm that occurred from 4th to 5th July 2014 is analyzed. Results show that the numerical experiment can well reproduce the temporal variability of heavy precipitation and successfully simulate accumulative precipitation and its evolution over the key rainstorm area. The simulated "rainbelt training" is consistent with observed "echo training" on both spatial structure and temporal evolution. The convective cells in the mesoscale convective belt propagated from southwest to northeast across the key rainstorm area, leading to large accumulative precipitation in this area. There existed convective instability in lower levels above the key rainstorm area, while strong ascending motion developed during the rainstorm process. Combined with abundant water vapor supply, the above condition was favorable for the formation and development of heavy rainstorm. The low-level jet (LLJ) provided sufficient energy for the rainstorm system, and the low-level convergence intensified, which was important for the maintenance of precipitation system and its eventual intensification to rainstorm. At its mature stage, the rainstorm system demonstrated vertically tilted structure with strong ascending motion in the key rainstorm area, which was favorable for the occurrence of rainstorm. In the decaying stage, unstable energy decreased and the rainstorm no longer had sufficient energy to sustain. The rapid weakening of LLJ resulted in smaller energy supply to the convective system, and the stratification tended to be stable in the middle and lower levels. The ascending motion weakened correspondingly, which made it hard for the convective system to maintain.